The Pedagogical Competence Predict From Academic Supervision, Kompentation and Work Motivation - Porniadi, Fiki; Kardoyo, Kardoyo; Yanto, Heri (Educational Management, 2019)
Pedagogic competence is one of the competencies that must be mastered by educators. Because with this competence the quality of education and more specifically learning will be more quality so that it is expected that the knowledge taught can be absorbed to the maximum. This study aims to determine and analyze the effect of supervisory supervision, compensation, and work motivation on pedagogical competence of non-civil servant Islamic education teachers in Pekalongan district. This research is a quantitative research with regression. This study uses a quantitative approach to see the causality relationship of several factors that influence the pedagogical competence of teachers. The population in this study was 52 non-civil servant PAI teachers. Data was collected by questionnaire and document study, after that the data was tested for validity and reliability. Furthermore, the data analyzed using path analysis with the help of SPSS AMOS 21. The results showed that supervision, compensation and motivation had an effect on the teacher's pedagogical competence. Suggestions put forward: (1) to supervisors to conduct routine and periodic supervision to teachers, (2) principals and government to allocate budgets to improve compensation received by non PNS teachers, (3) teachers must always motivate themselves to provide services the best for the main students at the time of learning. Valuation valuasi